1989
DOI: 10.1037/0096-3445.118.4.346
|View full text |Cite
|
Sign up to set email alerts
|

Serial position and set size in short-term memory: The time course of recognition.

Abstract: Subjects viewed sequentially presented lists of 3-6 words, which were followed by a recognition probe. Memory retrieval speed (dynamics) and strength were measured in an interruption speedaccuracy trade-off (SAT) procedure and a collateral reaction time (RT) procedure. In SAT, item strengths depended on serial position, but only two retrieval speeds were observed: a fast rate for the last item in the study list (a case of immediate repetition between study and test) and a slow rate for all other items that was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

52
553
6

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 365 publications
(619 citation statements)
references
References 61 publications
52
553
6
Order By: Relevance
“…Although it was originally argued that a serial search process was necessary to explain these results (Sternberg, 1966;Atkinson & Juola, 1974), a variety of parallel matching models provide excellent fits to this paradigm as well (Ratcliff, 1978;Hockley & Murdock, 1987;Nosofsky et al, 2011;Donkin & Nosofsky, 2012b;. At least at lags greater than one, there is no evidence for difference in retrieval dynamics, only for differences in asymptotic performance, consistent with the idea that, for the most part, recognition even from short lists is based on a parallel matching process rather than serial search (McElree & Dosher, 1989). …”
Section: Short-term Recognition and Lagsupporting
confidence: 52%
“…Although it was originally argued that a serial search process was necessary to explain these results (Sternberg, 1966;Atkinson & Juola, 1974), a variety of parallel matching models provide excellent fits to this paradigm as well (Ratcliff, 1978;Hockley & Murdock, 1987;Nosofsky et al, 2011;Donkin & Nosofsky, 2012b;. At least at lags greater than one, there is no evidence for difference in retrieval dynamics, only for differences in asymptotic performance, consistent with the idea that, for the most part, recognition even from short lists is based on a parallel matching process rather than serial search (McElree & Dosher, 1989). …”
Section: Short-term Recognition and Lagsupporting
confidence: 52%
“…This mechanism is possible only under a content-addressable system, where antecedent representations are elicited from memory via their content, and are directly accessible via the cues provided at the retrieval site. In this architecture, representations with varying degrees of distinctiveness are recovered in equal time, without a search (McElree and Dosher, 1989).…”
Section: Cue-based Retrieval Interference During Processing Of Ellipsismentioning
confidence: 99%
“…For example, in an item-recognition task in which a list of items is followed by a probe to be judged present in or absent from the list of items, it is typically observed that RTs to the last-presented item are faster than to any other item of the list (e.g., Burrows & Okada, 1971;McElree & Dosher, 1989;Nee & Jonides, 2008;Öztekin, Davachi, & McElree, 2010). The idea is that, at the end of the memory list, the final item is maintained in the focus of attention, resulting in speeded responses to probes that match that item.…”
Section: The Local Effect Of Refreshing On Wm Representationsmentioning
confidence: 99%